2010
DOI: 10.1007/s12550-010-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins levels in vegetable oils in Khartoum State, Sudan

Abstract: Vegetable oil (n = 81) for human consumption from Khartoum State in Sudan were analyzed for aflatoxins (AFs), using high-performance liquid chromatography (HPLC) with fluorescence detection following extraction with methanol:water (80:20) and clean-up using petroleum ether. Sampling included sesame oil (n = 14), peanut oil (n = 21), and sunflower oil (n = 19) purchased from retail shops, and mixed oil produced by two local manufacturers (factory A, n = 15; factory B, n = 12). AF contamination was found in 80/8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 13 publications
2
26
3
Order By: Relevance
“…The results for seven locations of Tanzania (Tables 2, 3, 4 and 5) corroborate reports from Sudan [6], Pakistan [19], Spain [20], Iran [21], and India [38, 39], which indicated that sunflower seeds and cakes were susceptible to aflatoxin contamination. The high aflatoxin levels in samples obtained from Dodoma, Morogoro, Babati and Singida towns may have resulted from a combination of drought and sub-optimal postharvest handling and storage of seeds and cakes [24, 31, 36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results for seven locations of Tanzania (Tables 2, 3, 4 and 5) corroborate reports from Sudan [6], Pakistan [19], Spain [20], Iran [21], and India [38, 39], which indicated that sunflower seeds and cakes were susceptible to aflatoxin contamination. The high aflatoxin levels in samples obtained from Dodoma, Morogoro, Babati and Singida towns may have resulted from a combination of drought and sub-optimal postharvest handling and storage of seeds and cakes [24, 31, 36].…”
Section: Discussionsupporting
confidence: 85%
“…In the past, human and animal exposure to dietary aflatoxins in Sub-Saharan Africa was considered to be mainly through consumption of maize and groundnuts. However, consumption of oilseeds such as sunflower, sesame, and cotton may also contribute significantly to the overall human and animal exposure to aflatoxins through food and feed [6–8]. …”
Section: Introductionmentioning
confidence: 99%
“…Stroka et al (1999) recommended employing aqueous methanol extractants specifically for AFB 1 , with aqueous acetone being a useful alternative. Methanol/water (80:20) has been utilized successfully for the extraction of AFs in various food commodities, such as spices (Fazekas et al 2005; O'Riordan and Wilkinson 2008), chilies (Santos et al 2010;Paterson 2007;Hierro et al 2008), wheat (Giray et al 2007), sorghum (Matumba et al 2010), and vegetable oil (Elzupir et al 2010). However, the use of acetonitrile/water (86:14) to increase polarity and extraction efficiency has been reported (Fu et al 2008;Iqbal et al 2010a, b) and acetonitrile/water (90:10) has been used for the extraction of AFs in spices (Akiyama et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The estimated/probable daily intake AF (E/P DIA of AF) is the result of multiplying estimated/probable daily intake of food (g) and the average T A B L E 1 Samples arrangement of Hx of AfB1-contaminated (μg/kg) vegetable oils in Sudan (Elzupir et al, 2010) levels of AF (μg/kg) and dividing them by the average body weight (kg).…”
Section: Discussionmentioning
confidence: 99%
“…AF in peanuts ranged from 26.6 to 853 μg/kg. These samples were collected from Khartoum in Sudan in 2009 and 2010 (Elzupir et al, 2011;Elzupir, Suliman, Ibrahim, Fadul, & Elhussein, 2010). The sorting of these results in ascending order and dividing them into groups, clarify the importance of highly contaminated food (HCF) samples (Figure 1), which should be subjected to treatments before use, even as animal feed.…”
mentioning
confidence: 99%